Gamble on the Uncertain. Negotiating Medical Decision-Making - Serra, Helena (Qualitative Sociology Review, 2016)
The aim of this paper is to analyze the medical decision-making process in the admission of patients into a Liver Transplant Program in a hospital in Lisbon, Portugal. The relationships and main strategies established among the medical specializations involved in this process will be investigated. The theoretical basis was drawn from medical sociology, in particular, from the social constructivist approaches, which highlight the relation between medical power and knowledge in the construction of medical decision-making. I attempt to elucidate the processes of negotiation through which a medical decision is constructed. The research methodology included non-participant observation and semi-structured interviews with participants from the two medical specializations of interest: liver surgeons and hepatologists. The management of risk and uncertainty in relation to patients’ access to liver transplantation is discussed and the strategic alliances that are formed during medical decision-making in search of consensus are investigated. The research findings show that medical practices and knowledge do not converge linearly to produce a coherent network of actions with a view to decision-making. Instead, medical decision-making is constructed through complex processes of negotiation. The different natures and levels of uncertainty and indetermination that are inherent in the social world of medicine have a fundamental influence on medical decision-making.